Correlation between Selenium Concentrations and Glutathione Peroxidase Activity in Serum and Human Prostate Tissue - Takata, Yumie (2009)
BACKGROUND: Low serum selenium concentration has been associated with increased risk of prostate cancer. A possible mechanism is through the antioxidant activity of selenoenzymes. However, the effect of selenium intake on selenoenzymes at target tissues is not well established. Hence, we investigated the correlation between serum and prostate tissue selenium concentrations and prostate tissue activity of glutathione peroxidase (GPX), a major selenoenzyme with antioxidant properties. METHODS: In an ongoing study investigating gene expression in prostate tissue, we measured serum selenium concentration in 98 men using atomic absorption spectrometry. Of these men, we selected 12 men with the highest and 12 men with the lowest serum selenium concentrations and measured selenium concentration and GPX activity in fresh frozen prostate tissue using the cyclic neutron activation analysis and a direct spectrophotometric procedure, respectively. RESULTS: The mean serum selenium concentrations among low and high selenium groups were 123.7 ± 5.9 μg/l and 196.7 ± 16.6 μg/l (p <.0001), respectively. The corresponding mean prostate tissue selenium concentrations were 1.39 ± 0.28 μg/g and 1.65 ± 0.42 μg/g (p = 0.08), resulting in a positive correlation between serum and prostate tissue selenium concentrations (r = 0.56, p = 0.02). The mean prostate tissue GPX activity was non-significantly greater in the low serum selenium group (32.2 ± 8.4 U/g protein) than in the high serum selenium group (29.6 ± 5.9 U/g protein) (p = 0.39) and it was not correlated with serum or prostate tissue selenium concentrations (r = −0.22, p = 0.37 for serum and r = −0.33, p = 0.18 for prostate tissue). CONCLUSION: Serum and prostate tissue selenium concentrations were moderately correlated. In this population with relatively high selenium concentration, neither prostate tissue nor serum selenium concentrations were associated with prostate tissue GPX activity.